PSVI-5 Treatment of Flunixin Meglumine and Prostaglandin E2 had no Effect on Corpora Lutea of Beef Cows. (21st September 2022) - Larson, Jamie E; Johnson, Tate; Swanson, Rebecca M; Messman, Riley D; Lemley, Caleb O
Abstract: Flunixin meglumine (FM) is a COX enzyme inhibitor and prostaglandin E2 (PGE) builds the corpus luteum (CL). However, the use of FM in conjunction with PGE has not been studied. The objective of this study was to determine effects of intravenous administration of FM and intravaginal release of PGE on characteristics of the CL and concentrations of PGE and progesterone in blood. Beef cows (n = 24, divided between two replicants over time) were synchronized using the Select Synch + CIDR protocol (expected estrus = d 0). Cows were randomly assigned to one of four treatment groups in a factorial arrangement, with 6 cows in each: Control, FM, PGE, or FM+PGE. Treatments were administered from d 13 to 19 (FM 2.2 mg/kg iv every 12 hr; PGE released in osmotic pump at 0.1 mL/d). Every other day from d 0 to 26, transrectal ultrasonography with color Doppler was used to measure size and blood perfusion of CL; images were later analyzed with ImageJ. Blood samples were collected via jugular venipuncture every other day from d 13 to 26 and later analyzed for concentrations of progesterone (P4; RIA) and PGE (ELISA). Data were analyzed using the mixed procedure of SAS 9.4 with day as a repeated measure; significance was declared when P ≤ 0.05. There were no interactions between FM and PGE, thus main effects of treatments were evaluated. There were no differences (P ≥ 0.164) in size, vessel density, or blood perfusion of CL between treatment groups. There were no differences (P ≥ 0.141) in concentrations of PGE or P4 between treatment groups. However, concentrations of P4 and PGE and density of blood vessels decreased by day (P ≤ 0.05). In conclusion, treatment with FM or PGE did not influence CL characteristics nor concentrations of P4 or PGE in circulation.